Development of a game with accessibility features for teaching lean healthcare - Gonçalves, Maria Clara Sampaio; Cerqueira, Eduardo Abreu Batista; Araujo, Andressa Clara Barbosa de; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2024)
Active methodologies of teaching bring the individual practical situations that encourage reflection and problem solving. Among them is the use of games, which seek to make learning more accessible and attractive. However, as much as this methodology works, it is not always inclusive. The application of games with accessibility features to teaching Lean Healthcare offers an engaging and inclusive approach to training healthcare professionals. This combination promotes the understanding of Lean principles in a practical and dynamic way, encouraging continuous improvement in healthcare service processes. The gamification strategy was then used, as it motivates the individual to learn, bringing better results. Thus, the present article presents a case study about the process of creating a game, entitled “Supply Chain Roulette”, which has an accessibility feature, developed so that a person with visual impairment can enjoy it without limitations. The results present the final game and its records as an industrial design and software, in addition to discussing the advantages of gamification in teaching Lean Healthcare.